"Overweight" Bodies, Real and Imagined - Gilleman, Sarah (Open textbook library., 2024)
This compilation gathers OER sources on body weight, nutrition, and movement, and it also problematizes the cultural meaning of these readings. Roughly, this anthology is divided into two parts--informational and theoretical--in depicting how medical research and journalism influence and are influenced by social stereotypes, constructed ideas about bodies, food, and individual choices within social systems.